Social Stories in mainstream schools for children with autism spectrum disorder: a feasibility randomised controlled trial. Issue 8 (11th August 2016) - Marshall, David; Wright, Barry; Allgar, Victoria; Adamson, Joy; Williams, Christine; Ainsworth, Hannah; Cook, Liz; Varley, Danielle; Hackney, Lisa; Dempster, Paul; Ali, Shehzad; Trepel, Dominic; et al.
Abstract : Objectives: To assess the feasibility of recruitment, retention, outcome measures and intervention training/delivery among teachers, parents and children. To calculate a sample size estimation for full trial. Design: A single-centre, unblinded, cluster feasibility randomised controlled trial examining Social Stories delivered within a school environment compared with an attentional control. Setting: 37 primary schools in York, UK. Participants: 50 participants were recruited and a cluster randomisation approach by school was examined. Participants were randomised into the treatment group (n=23) or a waiting list control group (n=27). Outcome measures: Acceptability and feasibility of the trial, intervention and of measurements required to assess outcomes in a definitive trial. Results: An assessment of the questionnaire completion rates indicated teachers would be most appropriate to complete the primary outcome measure. 2 outcome measures: the Social Responsiveness Scale (SRS)-2 and a goal-based measure showed both the highest levels of completion rates (above 80%) at the primary follow-up point (6 weeks postintervention) and captured relevant social and behaviour outcomes. Power calculations were based on these 2 outcome measures leading to a total proposed sample size of 180 participant groups. Conclusions: Results suggest that a future trial would be feasible to conduct and could inform the policy and practice of using Social Stories in mainstream schools. Trial registration number: ISRCTN96286707; Results.